Insomnia before and after childbirth: The risk of developing postpartum pain—A longitudinal population-based study. (March 2017) - Sivertsen, Børge; Petrie, Keith J.; Skogen, Jens Christoffer; Hysing, Mari; Eberhard-Gran, Malin
Abstract: Objective: To examine if insomnia before and after childbirth predicts the development of postpartum bodily pain. Methods: This study is part of a longitudinal cohort study, the Akershus Birth Cohort Study, which targeted all women giving birth at Akershus University Hospital in Norway. The current sample is comprised of 1480 women who participated at all three time points, yielding a participation rate of 32% of the 4662 women who originally consented to participate. The Bergen Insomnia Scale (BIS) was used to measure insomnia and a latent profile analysis (LPA) was used to identify subsets of women who shared a similar pattern of responses on the BIS-scale across the three time points. Pain was measured using the bodily pain scale, derived from the Primary Care Evaluation of Mental Disorders (PRIME-MD) and symptoms of depression were measured by the Edinburgh Postnatal Depression Scale (EPDS). Results: Using a latent profile analysis a three class model showed the best fit and identified one major group (55.6%) with a low BIS scores across all three time points, one group with intermediate BIS scores (32.9%), and a smaller group (11.5%) with higher BIS scores across all three times. The chronic high insomnia group had a 2.8-fold increased risk of reporting high levels of bodily pain. The chronic intermediate group was associated with a 2.2-fold increased risk of bodily pain at two years postpartum. Adjusting for demographics and lifestyle behaviors did not reduce any of the associations, while adjusting for depression significantly attenuated the associations. Additional adjustment for pain at eight weeks postpartum further reduced the magnitude of the associations, but both chronic intermediate insomnia and chronic high insomnia remained strongly associated with the onset of bodily pain in the fully adjusted models (RR = 1.75, 95% CI: 1.37–2.23) and RR = 1.63, 95% CI: 1.15–2.32, respectively). Conclusions: The high prevalence of insomnia among women during and after childbirth, in combination with the strong prospective association with impaired physical health, emphasizes the importance of adequately identifying, preventing and treating insomnia for this population.